AVAILABILITY OF PAEDIATRIC-EVALUATED FORMULATIONS IN SERBIA. Issue 1 (14th December 2015) - Božić, Bojana; Stupar, Sanja; Stupar, Duško; Bajčetić, Milica
Abstract : Background/Objective: A lack of appropriately evaluated medicines for paediatric population is a major problem as it often leads to inadequate treatment of children. The aim of this study was to investigate the availability of paediatric formulations labelled for children up to the age of 12 years old in Serbia in 2013, as well as the availability of paediatric medicines reimbursed by the Republic Health Insurance Fund (RFZO). The availability of paediatric formulations in Serbia is also compared with the 'Model List of Essential Medicines for Children' by World Health Organization's (WHO). Methods: Sources of information about medicines were: the Summary of Product Characteristics (SmPc), RFZO Drug Lists, WHO Model Lists of Essential Medicines for Children, and Serbia's official drug registry, editions 2013. Results: In Serbia only 49% (496) of INN drugs were suitable for children of which only 66% were licensed for paediatric use. Majority of licensed drugs were parenteral formulations, 57%, followed by drugs for local use, 28%, and formulations for oral use, 23%. The lowest availability of medicines was for children 0–27 days old. From the total number of licensed medicines for children up to 12 years old, the Republic Fund for Health Insurance covers 64% of drugs and from each therapeutic group at least one medicine is reimbursed by fund. The availability of WHO essential medicines for children in Serbia was 51%, from which 92% were licensed for paediatric use. Conclusion: Our study showed that from already unsatisfactory number of available drugs for children only 66% is licensed. Limited availability of paediatric medicines for all ages of this population and for a broad range of therapeutic areas still represents a cause for concern in our country.